Experience curves as a planning tool - Cedric G. Robinson (South African Journal of Business Management, 1982)
In this article, the first of a series of two articles, the Boston Consulting Group's use of the experience curve as a strategic planning tool is explained. The experience effect is described and differences between learning curves, experience curves and economies of scale are highlighted. The effect of experience on product costs is described: costs don't just decline, they must be managed. The effects of experience on costs and prices are quantified, and sources of the experience effect amenable to strategic management are given. Strategic implications for competitive interaction using company experience are considered. (The second article, to be published, will explode some myths associated with the idyll. Perrhic victories in the quest for market share will be described and practical problems in applying the experience effect will be highlighted).
Keywords: 650